UPAYA MENUMBUHKAN KARAKTER CINTA LINGKUNGAN DALAM PERSPEKTIF PEMIKIRAN PENDIDIKAN ISLAM - Hajiannor Hajiannor (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2021)
ABSTRACTNature is the locus of manifestation of all divine names and attributes, so destroying nature means destroying the "face" or sign (verse) of God on earth, violating His mandate to protect, and violating the mandate of creation. The preservation of the natural environment requires care and compassion. Overexploitation, greed and mistreatment of some humans towards nature will eventually be able to make humans miserable themselves. Efforts to grow the character of love for the environment are needed for the establishment of harmonious relations with other creatures as fellow creations. Responsive theological thinking is needed to build an attitude of caring for others. With it, humans as the main cosmos of this nature and also as His caliph on earth are able to utilize and manage the universe for the good and benefit of all His creatures.KEYWORDS: Love the environment; Exploitation; Sustainability of Nature; Theology.ABSTRAKAlam adalah lokus manifestasi dari seluruh nama-nama dan sifat-sifat Ilahi, maka merusak alam berarti merusak “wajah” atau tanda (ayat) Tuhan di muka bumi, melanggar amanah-Nya untuk menjaga, dan melanggar amanah ciptaan. Penjagaan kelestarian alam lingkungan menghajatkan kepedulian dan kasih sayang. Eksploitasi berlebihan, keserakahan dan perlakuan buruk sebagian manusia terhadap alam pada akhirnya akan dapat menyengsarakan manusia itu sendiri. Upaya menumbuhkan karakter cinta lingkungan diperlukan untuk terjalinnya relasi yang harmoni secara maslahat dengan makhluk yang lain sebagai sesama ciptaan-Nya. Pemikiran teologi yang responsif diperlukan bagi terbangunnya sikap peduli kepada selainnya. Dengannya manusia sebagai pengkosmos utama alam ini dan juga sebagai khalifah-Nya di muka bumi mampu memanfaatkan dan mengelola alam semesta untuk kebaikan dan maslahat bagi semua makhluk-Nya.KATA KUNCI: Cinta Lingkungan; Eksploitasi; Kelestarian Alam; Teologi.